N6-Methyladenosine Associated Silencing of miR-193b Promotes Cervical Cancer Aggressiveness by Targeting CCND1 - Huang, Chunxian; Liang, Jinxiao; Lin, Shaodan; Wang, Dongyan; Xie, Qingsheng; Lin, Zhongqiu; Yao, Tingting (Frontiers in Oncology, 2021)
Objective Cervical cancer is a frequently encountered gynecological malignancy as a major contributor to cancer-related deaths in women. This study focuses on how miR-193b promotes cervical cancer aggressiveness as well as the role of m6A in miR-193b silencing. Methods Cervical cancer samples and the matching adjacent normal cervical tissues were used to determine the significance of miR-193b in cervical cancer. The CCK-8 assay, cell cycle analysis, qRT-PCR, Western blot assay, IHC, RIP, and xenograft models were utilized to explore the impact of miR-193b in cervical cancer and how m6A regulates miR-193b expression. Luciferase reporter assays, qRT-PCR, and Western blotting were enlisted to study the interaction between miR-193b and CCND1. Results Our study suggested that lower miR-193b expressions were strongly linked to more advanced cervical cancer stages and the presence of deeper stromal invasion. miR-193b functions as a tumor suppressor that is regulated by m6A methylation in cervical tumors. METTL3 modulates miR-193b mature process in an m6A-dependent manner. Reintroduction of miR-193b profoundly inhibits tumorigenesis of cervical cancer cells both in vivo and in vitro through CCND1 targeting. Conclusions m6A associated downregulation of miR-193b promotes cervical cancer aggressiveness by targeting CCND1.